A clinical and functional system for patients with accommodation disorders subjected to excimer laser correction of hypermetropia - O. S. Kuznetsova; S. V. Balalin (Российский офтальмологический журнал)
Purpose: to develop a clinical and functional rehabilitation system for patients with mild and moderate hyperopia and accommodation disorders before and after FemtoLASIK surgery and to assess its effectiveness.Material and methods. 234 patients (234 eyes) with the above conditions, aged 25 to 30 (mean age 27.9 ± 1.2 years) were divided into 2 groups. The control group included 114 patients (114 eyes) who received no prevention measures or accommodation disorders treatment, while the main group (120 patients, 120 eyes) received clinical and functional rehabilitation before and after FemtoLASIK.Results. The “false myopization” syndrome observed in the main group was 14.2% lower than in the control group. A week after FemtoLASIK, the normalization of accommodation parameters was achieved in 57.5% of the main group cases, and combined accommodation disorders occurred 2.37 less frequently than in the control group. Weak accommodation in patients of this group was 30% less than in the control group. Habitually excessive accommodation in the control group was 2.45 times more frequent than in the main group. According to the CISS test questionnaire, the mean values of indices for the main group patients reached the normal level one month after FemtoLASIK whilst the control group required 6 months.Conclusion. The clinical and functional rehabilitation system in patients with mild and moderate hyperopia and accommodation disorders applied before and after FemtoLASIK helps achieve maximum clinical and functional results 1 month after the operation and yields the best results in accommodation disorders treatment.